Essays on sub-optimal fiscal policy responses in sub-Saharan African countries - Kufuor, Nana Kwabena (2012)
The actions of governments are instrumental in economic development, and an important lever of policy is fiscal policy. Taxation and spending cannot only promote economic development but inhibit progress and retard the process, and nowhere is this most evident than in sub-Saharan Africa (SSA), which is the focus of this study. Promoting economic development therefore requires that policies that inhibit the process are identified and addressed. In this light, this thesis investigates two common features of fiscal policy in developing countries that may slow down economic development: the first is that government consumption is pro-cyclical even though increasing (reducing) spending in response to increases (decreases) in income worsens income fluctuations. The second feature is that the budget deficit (budget balance) increases (decreases) in response to aid inflows.